2016
DOI: 10.1016/j.smr.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Communicating via photographs: A gendered analysis of Olympic athletes’ visual self-presentation on Instagram

Abstract: A gendered analysis of Olympic athletes' visual self-presentation on InstagramResubmitted to Sport Management Review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
2
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 52 publications
13
156
2
8
Order By: Relevance
“…Considering the importance of athletes' social media use, numerous publications have examined professional and elite athletes' personal branding efforts carried out via social media and found that they actively were presenting and portraying themselves to develop their personal brands (Agyemang & Williams, 2016;Coche, 2014;Davies & Mudrick, 2017;Geurin, 2017;Geurin-Eagleman & Burch, 2016;Green, 2016;Hodge & Walker, 2015). For example, Hodge and Walker (2015) discovered that professional golfers acknowledged the importance of having strong personal branding skills but perceived a number of challenges to building an effective person-JADE Bowling Green State University -https://scholarworks.bgsu.edu/jade/ al brand; these challenges included a lack of knowledge, time, and support.…”
Section: Athlete Branding and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the importance of athletes' social media use, numerous publications have examined professional and elite athletes' personal branding efforts carried out via social media and found that they actively were presenting and portraying themselves to develop their personal brands (Agyemang & Williams, 2016;Coche, 2014;Davies & Mudrick, 2017;Geurin, 2017;Geurin-Eagleman & Burch, 2016;Green, 2016;Hodge & Walker, 2015). For example, Hodge and Walker (2015) discovered that professional golfers acknowledged the importance of having strong personal branding skills but perceived a number of challenges to building an effective person-JADE Bowling Green State University -https://scholarworks.bgsu.edu/jade/ al brand; these challenges included a lack of knowledge, time, and support.…”
Section: Athlete Branding and Social Mediamentioning
confidence: 99%
“…Self-presentation theory (Goffman, 1959) has been widely used in the study of social media research in regard to how people utilize its functions to present or represent various content (e.g., Geurin-Eagleman & Burch, 2016;Marshall, 2010). Self-presentation is defined as a mechanism by which wanted information can be delivered to others.…”
Section: Self-presentation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…14). Academic research of the social media platform includes studies of self-presentation by athletes (Geurin-Eagleman & Burch, 2016;Smith & Sanderson, 2015), how fans use the platform to engage with teams (Kim & Hull, 2017), and how the hashtag #SheBelieves was used to frame coverage of the U.S. Women's Soccer Team during the 2015 FIFA World Cup (Pegoraro, Comeau, & Frederick, 2017). Instagram use by organizations and companies has also been examined, including the degree to which Major League Baseball (MLB) teams demonstrate corporate social responsibility through the platform (Hull & Kim, 2016).…”
Section: Instagram and Social Sharingmentioning
confidence: 99%
“…Las comunicaciones de marca, que antes eran controladas por las empresas, ahora están pasando a ser controladas gradualmente por los consumidores (Aaker, 2009). Schivinski y Dabrowski (2016) argumentan que, en los últimos años con el rápido crecimiento de los medios sociales, todas las investigaciones empíricas se han centrado en temas relacionados con la comunicación de boca en boca electrónica (Bambauer-Sachse y Mangold, 2011;Sarmiento, 2015;Sarmiento, 2017b), con comunidades de marca (Algesheimer et al, 2005) o con el contenido generado por el usuario (Geurin y Burch, 2016). Tras haber hecho una revisión de la literatura existente sobre la comunicación que las marcas realizan a través de los medios sociales, nos hemos encontrado con el primer gap; solo hemos podido encontrar un trabajo, el realizado por los autores Schivinski y Dabrowski (2016), que analiza la influencia de la comunicación de marca sobre los consumidores.…”
Section: Introductionunclassified